Risk factors for the isolation of a third generation cephalosporin resistant strain in patients with community-acquired Enterobacteriaceae bacteraemia. Issue 2 (February 2016) - Ortega, M.; Soriano, A.; Marco, F.; Almela, M.; Martínez, J.A.; Morata, L.; Cobos-Trigueros, N.; de la Calle, C.; Mensa, J.
Highlights: CTX-R Enterobacteriaceae cause frequently infections in community setting. This has important implications for the management of these infections. We studied 2, 989 Enterobacteriaceae community-acquired bacteraemia. 178 (6%) strains were CTX-R (153 E. coli and 25 Klebsiella spp). Related factors with isolating a CTX -R strain are frequent in elderly people.